PERSPEKTIF TEORI AKUNTANSI KEUANGAN TERHADAP MASALAH LINGKUNGAN - Abdul Halim (UGM, 1999)
Environmental problem is a universal and complex problem. Many problems emerge in relation to the environmental problems such as air pollution, soil contaminations etc. Those are not only the governments' resposibility but also the all of human life responsibility. Accordingly, everyone should have responsibility and concern to those problems. Business enterprises, professionals, and so on, of course should also concern and involve to help reducing the environmental problems.